The Main Determinants of Inflation in Nigeria - Moser, Gary. (Washington, D.C. : International Monetary Fund, 1994)
This paper provides a selective review of the literature on the determinants of inflation in Nigeria, analyzes the dominant factors influencing inflation, presents the empirical results of a reduced-form elasticities model, and discusses the policy implications of the empirical results. The results of this analysis confirm the basic findings of earlier studies, namely that monetary expansion, driven mainly by expansionary fiscal policies, explains to a large degree the inflationary process in Nigeria. Other important factors are the devaluation of the naira and agroclimatic conditions. With respect to the depreciation of the naira, it was found that concurrent fiscal and monetary policies had a major influence on its impact on inflation. Given the considerable role of food commodities in the CPI, agroclimatic conditions (rainfall) were found to play a significant role in overall movements in prices and should be fully taken into consideration in any analysis of the inflationary process in Nigeria.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet